2015
DOI: 10.1002/lno.10067
|View full text |Cite
|
Sign up to set email alerts
|

Microgeographic adaptation to toxic cyanobacteria in two aquatic grazers

Abstract: The hypothesis that zooplankton display local adaptations to toxic cyanobacteria was tested by investigating the performance of 24 clones from six populations of the large-bodied Daphnia pulex and 13 clones from four populations of the small-bodied Chydorus sphaericus. They were fed a pure nutritious green alga Chlorella pyrenoidosa (good food) and a mixed diet with a toxic cyanobacterium Microcystis aeruginosa (poor food). The grazer performances feeding on the poor food significantly differed among their pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 31 publications
5
20
0
Order By: Relevance
“…On the other hand, zooplankton often exist mutually with harmful algal blooms (HABs), suggesting that they have multiple abilities to behaviorally reduce the ingestion of hazardous doses and to be physiologically tolerant to the ingested toxin. In line with the previous studies (Hietala et al ; Chislock et al ; Jiang et al , ), the present population‐level results clearly showed clonal variation in Daphnia fitness in response to toxic Microcystis . Of note, the clones were cultured individually under identical conditions.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, zooplankton often exist mutually with harmful algal blooms (HABs), suggesting that they have multiple abilities to behaviorally reduce the ingestion of hazardous doses and to be physiologically tolerant to the ingested toxin. In line with the previous studies (Hietala et al ; Chislock et al ; Jiang et al , ), the present population‐level results clearly showed clonal variation in Daphnia fitness in response to toxic Microcystis . Of note, the clones were cultured individually under identical conditions.…”
Section: Discussionsupporting
confidence: 93%
“…) and for Daphnia pulex from small Chinese ponds and rivers with different trophic states (Jiang et al. ). However, cyanobacteria tolerance is costly and might be associated with tradeoffs such as being more vulnerable to starvation for more tolerant individuals (Hairston et al.…”
Section: Introductionmentioning
confidence: 99%
“…The green alga Chlorella pyrenoidosa (Chlorellaceae) (FACHB-15) and the microcystin-producing cyanobacterium Microcystis aeruginosa (Microcystaceae) (FACHB-905) were obtained from the Freshwater Algae Culture Collection at the Institute of Hydrobiology (FACHB-collection), the Chinese Academy of Sciences. The FACHB-905 strain produces microcystin-LR and microcystin-RR at a total concentration of 24 fg cell À1 (Jiang et al, 2015). The cultures were grown in BG-11 medium at 25°C under fluorescent light at 50 lmol m À2 s À1 on a 12:12 light:dark cycle.…”
Section: Plankton Collection and Incubationmentioning
confidence: 99%
“…Total microcystin concentration was measured with an enzyme linked immunosorbent assay (ELISA). The detailed ELISA protocol has been described in our previous study (Jiang et al, 2015).…”
Section: Sediment Collection and Analysesmentioning
confidence: 99%